Influencia del apego parental en la elección de pareja en mujeres de 25 a 35 años de la Ciudadela “El Chorrillo” del Cantón Babahoyo - Andrade Bravo, Natasha Mishell (2025)
Objective: To analyze the influence of parental attachment on the personal and professional decisions of women aged 25 to 35 years from the citadel “el chorrillo” in the Babahoyo canton. Materials and methods: Quantitative, non-experimental study, with a descriptive and correlational design, carried out among women aged 25 to 35 years from the citadel "El Chorrillo". The research was carried out with an adjusted sample of 123 through formula, guaranteeing representative results with a confidence level of 95%. Results: In a sample of 123 women it was shown that a majority of women value independence and emotional security in relationships, with 47.2% prioritizing emotional security and 56.1% highlighting the importance of emotional compatibility. Regarding parental attachment, 68.3% recognized the influence of their parents' values on their current decisions, while 41.5% felt insecure about how their parents responded to their emotional needs. Conclusions: The study shows that parental attachment influences adult relationships, with the majority valuing security and emotional compatibility. Some women have difficulty trusting their partners, reflecting anxious or avoidant attachment patterns. Childhood experiences, such as emotional insecurity, impact the ability to form healthy relationships. This study highlights the need for psychoeducational interventions aimed at strengthening emotional security from childhood to foster more balanced emotional relationships in adulthood.